Clinical Efficacy of TM02® in Allergic Rhinitis: Significant Symptom Alleviation Associated with IL-5 Downregulation and Reduced Allergic Inflammation - Hao-Dong Tan; Sien-Hui Tan; Boon-Hong Kong; Chee-Kuan Wong; Revadi Govindaraju; Tengku Ahmad Shahrizal Tengku Omar; Shin-Yee Fung (Current Issues in Molecular Biology, 2026)
Allergic rhinitis (AR) is a chronic inflammatory disease that substantially affects quality of life. Despite available therapies, symptom control remains suboptimal owing to treatment burden. Cultivated sclerotium of Lignosus rhinocerus (TM02®), known for its allergy-dampening bioactivities, is a promising adjunctive AR treatment. A randomized, double-blinded clinical trial was conducted in 108 AR patients, who received either TM02® or placebo for 30 days. Primary outcomes consisted of Total Nasal Symptom Score (TNSS), reflective of past 12 h and 2 weeks (TNSS12hrs and TNSS2wks), and the Allergic Rhinitis Control Test (ARCT). The secondary endpoints were the peripheral immune biomarkers: IgE, IFNγ, IL-4, IL-5 and IL-13. Safety was assessed with adverse events (AEs) and full blood-counting analyses. Statistical analysis was performed using generalized estimating equation (GEE) in the modified per-protocol (mPP). mPP analysis (N_TM02® = 25; N_placebo = 31) demonstrated significant treatment effectiveness of TM02® in total TNSS12hrs, total TNSS2wks, and ARCT (β = −3.70, p-value < 0.001; β = −4.44, p-value < 0.001; and β = 3.89, p-value = 0.017, respectively). Secondary endpoint analysis did not reveal significant changes. However, a positive associative pattern (β = 14.94; p-value = 0.003) was observed between TNSS2wks and IL-5 level changes. There were no significant differences in AE incidences and laboratory safety biomarkers between treatment arms. The present study revealed that TM02® reduced AR symptom severity with minimal adverse effects. The underlying mechanism may involve the modulation of IL-5 levels and allergic inflammation. Overall, TM02® is a potential adjunctive or complementary treatment option for AR with persistent symptoms.